Pendidikan Bisnis, Bisnis Pendidikan - Sumargo, Bagus (Journal the Winners: Economics, Business, Management, and Information System Journal, 2004)
The implication of educations decentralization implies that colleges have authority to manage the whole education process. Nevertheless, the education have to be conducted professionally. The colleges should determine one study program havingÂ  business oriented. Therefore, the education is driven into business purposes.